Hubungan Dukungan Sosial dan Kecerdasan Emosi dengan Perilaku Prososial - Harmalis Harmalis (Tabularasa: Jurnal Ilmiah Magister Psikologi, 2023)
This study aims to examine the relationship of social support and emotional intelligence with prosocial behavior in students of State Junior High School 3 in Binjai City. The sampling technique in this study is simple random sampling technique. The researcher determines the sample by random number from the population number of the population in each class, and obtained a sample of 177 students. The results of the study with multiple regression analysis using SPSS. Version.18 shows the price of the correlation coefficient R = 0.763 with P = 0.000 0.05. So it can be concluded that together social support and emotional intelligence variables are significantly correlated with prosocial behavior variables. Effective contribution of variables X1 and X2 to Y is indicated by the price of R2 = 0.582, which means that the variables of social support and emotional intelligence together contribute 58.2% to prosocial behavior. Partially the results of statistical calculations show the price of t = 6.511 at P = 0.00 for the correlation of social support variables with prosocial behavior. Price t = 7.211 at P = 0.00 for the correlation of emotional intelligence variables with prosocial behavior, meaning that partially social support variables and emotional intelligence variables also correlate significantly with prosocial behavior.